Spatial Cell Disparity in the Colonial Choanoflagellate Salpingoeca rosetta - Naumann, Benjamin; Burkhardt, Pawel (Frontiers in Cell and Developmental Biology, 2019)
Choanoflagellates are the closest unicellular relatives of animals (Metazoa). These tiny protists display complex life histories that include sessile as well as different pelagic stages. Some choanoflagellates have the ability to form colonies as well. Up until recently, these colonies have been described to consist of mostly identical cells showing no spatial cell differentiation, which supported the traditional view that spatial cell differentiation, leading to specific cell types in animals, evolved after the split of the last common ancestor of the Choanoflagellata and Metazoa. The recent discovery of single cells in colonies of the choanoflagellate Salpingoeca rosetta that exhibit unique cell morphologies challenges this traditional view. We have now reanalyzed TEM serial sections, aiming to determine the degree of similarity of S. rosetta cells within a rosette colony. We investigated cell morphologies and nuclear, mitochondrial and food vacuole volumes of 40 individual cells from four different S. rosetta rosette colonies and compared our findings to previously published data on sponge choanocytes. Our analysis show that cells in a choanoflagellate colony differ from each other in respect to cell morphology and content ratios of nuclei, mitochondria and food vacuoles. Furthermore, cell disparity within S. rosetta colonies is higher compared to cell disparity within sponge choanocytes. Moreover, we discovered the presence of plasma membrane contacts between colonial cells in addition to already described intercellular bridges and filo-/pseudopodial contacts. Our findings indicate that the last common ancestor of Choanoflagellata and Metazoa might have possessed plasma membrane contacts and spatial cell disparity during colonial life history stages.